The Internationalisation of Portuguese SMEs - Pereira, Elisabeth T. (2007)
This paper begins with an overview of the history of Portuguese entrepreneurship over the last century. Next, the study analyses the importance of SMEs in actual competitive environment of international markets, investigating the case of the internationalisation of Portuguese businesses (processes, modes of entry, strategies and intentions and reasons of internationalisation) and the principal features of Portuguese entrepreneurship and SMEs on domestic and foreign markets.